PERAN REGULASI EMOSI DALAM HUBUNGAN ANTARA TRAUMA FINANSIAL DAN FINANCIAL ANXIETY PADA MAHASISWA - Wiwin Yuliani; Afridha Batubara; Mohammad Handy Wijaya; Muhammad Irvan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Financial anxiety is a psychological problem commonly experienced by university students due to economic pressures and negative experiences related to financial conditions. Although the relationships among financial conditions, emotion regulation, and psychological well-being have been widely examined, the psychological mechanisms underlying the association between financial trauma and financial anxiety among university students remain poorly understood. Based on the Process Model of Emotion Regulation, which explains that individuals can manage emotional responses through regulation processes and changes in the appraisal of stressful experiences, this study aimed to examine the role of emotion regulation in explaining the relationship between financial trauma and financial anxiety among university students. This study employed a quantitative correlational approach with a cross-sectional design involving 45 students from several universities in West Java selected through simple random sampling. Data were collected using a financial trauma scale, the Emotion Regulation Questionnaire, and a financial anxiety scale. Data were analyzed using Pearson correlation, multiple regression, and simple mediation analysis. The results showed that financial trauma was associated with higher levels of financial anxiety, whereas better emotion regulation was associated with lower levels of financial anxiety. Further analysis indicated that emotion regulation played a partial mediating role in the relationship between financial trauma and financial anxiety. However, because this study used a cross-sectional design, the findings cannot be interpreted as demonstrating causal relationships. These findings suggest that emotion regulation is a relevant psychological factor for understanding financial anxiety among university students and may provide a basis for developing intervention programs that integrate emotion regulation skills with financial management education. ABSTRAK Kecemasan finansial merupakan masalah psikologis yang banyak dialami mahasiswa akibat tekanan ekonomi dan pengalaman negatif terkait keuangan. Meskipun hubungan antara kondisi finansial, regulasi emosi, dan kesejahteraan psikologis telah banyak dikaji, mekanisme psikologis yang menjelaskan keterkaitan antara trauma finansial dan financial anxiety pada mahasiswa masih belum banyak dipahami. Berdasarkan Process Model of Emotion Regulation yang menjelaskan bahwa individu dapat mengelola respons emosional melalui proses regulasi dan perubahan penilaian terhadap pengalaman yang menekan, penelitian ini bertujuan menganalisis peran regulasi emosi dalam menjelaskan hubungan antara trauma finansial dan financial anxiety pada mahasiswa. Penelitian ini menggunakan pendekatan kuantitatif korelasional dengan desain cross-sectional yang melibatkan 45 mahasiswa dari beberapa perguruan tinggi di Jawa Barat yang dipilih melalui teknik acak sederhana. Data dikumpulkan menggunakan skala trauma finansial, Emotion Regulation Questionnaire, dan skala financial anxiety. Data dianalisis menggunakan korelasi Pearson, regresi berganda, dan analisis mediasi sederhana. Hasil penelitian menunjukkan bahwa trauma finansial berkaitan dengan tingkat financial anxiety yang lebih tinggi, sedangkan regulasi emosi yang lebih baik berkaitan dengan tingkat financial anxiety yang lebih rendah. Analisis lebih lanjut menunjukkan bahwa regulasi emosi memiliki peran mediasi parsial dalam hubungan antara trauma finansial dan financial anxiety. Namun, karena penelitian menggunakan desain cross-sectional, temuan ini tidak dapat diinterpretasikan sebagai hubungan sebab-akibat. Temuan penelitian menunjukkan bahwa regulasi emosi merupakan faktor psikologis yang relevan dalam memahami financial anxiety mahasiswa dan dapat menjadi dasar pengembangan program intervensi yang mengintegrasikan keterampilan regulasi emosi dengan edukasi pengelolaan keuangan.